Religious Freedom and the Law: A Reality or Pipe Dream for Prisoners in South Africa? - H. Puleng Motlalekgosi (Journal for the Study of Religion)
Freedom of religion, like other human rights, must be respected, protected, and promoted by relevant and entrusted authorities to comply with legitimate laws, applicable to a particular environment. In South Africa, the Correctional Services Act 111 of 1998 as amended, the White Paper on Corrections in South Africa of 2005, and internal policies are intended to make provision for prisoners' freedom of religion in the correctional services environment. These essentially give effect to the Constitution of the Republic of South Africa of 1996, emanating from pertinent international and African continental instruments. Through an analytic design of change over time, this essay seeks to conduct an analysis of prisoners' freedom of religion in South Africa. This analysis is based on the Department of Correctional Services' annual reports published between 1997 and 2016 and the general conditions of prisons in South Africa. The finding of this study reveals a violation of the right of prisoners to freedom of religion by the South African correctional authority.